Penerapan Metode Desain Tata Letak Gudang dan Klasifikasi ABC untuk Mengoptimalkan Penyimpanan Barang Part Assembly Panel Surya di PT. XYZ - Febrianto Maulana, Ferdy; Nurcahya Hidayat, Fauziah; Fauzi, Muchammad (Kohesi: Jurnal Sains dan Teknologi, 2025)
Efficient product design is one of the most important factors in improving the operational performance of a company, especially in the manufacturing sector. The purpose of this study is to optimize the layout of the solar panel assembly warehouse at PT. XYZ using two methods: the ABC classification method and the warehouse layout design method. To minimize the time and cost involved in the goods development process, the warehouse layout design method is used to determine the ideal placement of goods in the warehouse. In contrast, the ABC classification is used to group goods according to their value and frequency of use in order to prioritize the delivery of goods with high Orders/days and to determine the high value of the goods in question. The results of this study indicate that the application of both methods can improve the efficiency of storage space and accelerate the existing barangay development process, which has a significant impact on reducing operational costs and increasing productivity. This study offers strategic recommendations to improve the warehouse layout design of PT. XYZ in order to improve operational efficiency and effectiveness.